2013
DOI: 10.3109/09638288.2012.742677
|View full text |Cite
|
Sign up to set email alerts
|

People with dementia in long-term care facilities: an exploratory study of their activities and participation

Abstract: People with dementia living in long-term care facilities have severe activities limitation and participation restriction. Rehabilitation through engagement in activities and enhancement of participation seems to be crucial for this population. A multidimensional characterisation of activities and participation is recommended to inform the design and implementation of rehabilitation. Mobility was the most affected domain, highlighting the need for specific rehabilitation, as mobility restrictions are associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…approximately three points higher than controls. 15,16 In our retrospective cohort, we found that there was a statistically significant difference in WHODAS scores between women with and without SMM. 7 However, there are still many gaps in our understanding of such results, as there is no baseline score or threshold to determine the clinical significance of these findings.…”
Section: Discussionmentioning
confidence: 71%
“…approximately three points higher than controls. 15,16 In our retrospective cohort, we found that there was a statistically significant difference in WHODAS scores between women with and without SMM. 7 However, there are still many gaps in our understanding of such results, as there is no baseline score or threshold to determine the clinical significance of these findings.…”
Section: Discussionmentioning
confidence: 71%
“…Problems related to daily person transfer situations (e.g. sit-to-stand transfer, bedside transfer) are the most common precipitating factors for institutionalisation among people with dementia, [2,4,5] alongside behavioural problems [6].…”
Section: Introductionmentioning
confidence: 99%
“…This may affect their ability to relate to others, which thus contributes to reduced social participation (Sorensen, Waldorff and Waldemar 2008). People with cognitive problems experience increasing difficulties with participating in community activities (Rocha et al 2013). Social participation continues to decrease as cognitive problems progress (Barberger-Gateau et al 2002; Muo et al 2005).…”
Section: Introductionmentioning
confidence: 99%